The Irish in Quebec: An Introduction to the Historiography - Gossage, Peter (Labour / Le Travail, 1995)
The article reviews the book, "The Irish in Quebec: An Introduction to the Historiography," by Robert J. Grace.
Keywords: BOOKS -- Reviews; GRACE, Robert J.; Historiography; IRISH in Quebec: An Introduction to the Historiography, The (Book); Nonfiction